HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG KANKER PAYUDARA DENGAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA DI SMA NEGERI 1 DELI TUA KABUPATEN DELI SERDANG TAHUN 2024 - Krisna, Putri; Chairani, shinta Andria; Br Bangun, Sofia Eliasari (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2024)
Adolescent girls have the potential to experience breast abnormalities because hormonal activity, especially the hormone estrogen, is currently unstable. Adolescent girls who get their first menstruation earlier have exposure to the hormone estrogen for longer in their lives so the potential for breast abnormalities is quite large. Self-Examination of the Breasts (BSE) is a technique for recognizing the normal condition of the breasts and determining whether there are lumps that can trigger tumors or breast cancer independently. To determine the relationship between knowledge and attitudes about breast cancer with breast self-examination (BSE) among adolescents at SMA Negeri 1 Deli Tua, Deli Serdang Regency in 2024. The type of research used is the type of design used is a cross-sectional approach, namely research that emphasizes the time of measurement. or analyze data in one go. The population of respondents will be used as a sample, namely total sampling, where all teenagers in SMA Negeri 1 class X and XI Deli Tua Deli Serdang Regency are 30 people. The results of this research are knowledge with a p-value of 0.003, which means there is a relationship between knowledge and breast self-examination (BSE) and attitude p-value 0.003, which means there is a relationship between knowledge and breast self-examination (BSE). From the results of this research, it is hoped that breast self-examination (BSE) can be used as an effort to detect breast cancer early.